Some new morphemes in Philippine Languages - Lopez, Cecilio (The Archive, 2025)
A few years ago I became interested in (a) the reflexes of Dempwolff’s doublet reconstructions in the Philippine Languages1 and (b) in non-productive infixes in the Indonesian languages.2 To gather the basic data I went through Dempwolff’s three volume work (Vergleichende Lautlehre.).3 In the process of gathering the data, some of Dempwolff’s reconstructions called to mind equivalents in the Philippine languages which are not reflexes of his reconstructions.4 My curiosity was aroused and simultaneous with the data I was gathering for (a) and (b) above, I made a list of the equivalents which I came to in a random manner and by accident. This list is the subject of this paper which, at this stage, makes no claim of exhaustiveness. And it is not the intention either to use a diagnostic vocabulary.